Critical incidents of quality orientation in lower and middle management. Issue 5 (8th August 2016) - Heine, Ina; Schmitt, Robert; Beaujean, Patrick
Abstract : Purpose: The purpose of the present research is the identification of critical management behaviour regarding quality orientation in organisations. Design/methodology/approach: In order to describe how quality orientation is manifested in management behaviour, the critical incident technique was chosen. First, quality orientation was defined based on an extensive literature review. Then, critical incidents that represent a behavioural manifestation of each dimension were derived through a deductive approach. Lastly, an expert group consisting of scientists and practitioners were asked to categorise the critical incidents and evaluate their practical relevance and completeness. Findings: The results show that the construct quality orientation is related to the five variables internal customer focus, external customer focus, continuous improvement orientation, systems-thinking perspective, and data-driven. For each variable four critical incidents were developed and evaluated by the expert group. Analyses of the data show fair agreement between the raters with an overall agreement index of .38 (based on Cohen's Kappa). Originality/value: The results of the present study can be used to support managers in understanding and practising behaviour critical to organisation-wide quality and thereby improving working conditions as well as business results.